Electrochemical Detection of Thiamine using Differential Pulse Voltammetry at PEDOT:PSS modified Glassy Carbon Electrode - Ulfiatun Nisa; Aninda Naszwa Kuswanto; Nur Zamilah; Budi Riza Putra; Wulan Tri Wahyuni (Analit: Analytical and Environmental Chemistry, 2022)
The development of easy and rapid detection method for vitamin in food is interesting to study because this compound is an essential nutrient to maintain the metabolism in the human body. Herein, this work aims to detect vitamin B1 (thiamine) content in the supplement of commercial vitamin by differential pulse voltammetry technique using a glassy carbon electrode modified poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT: PSS) and compare the results with the spectrophotometry UV-Vis. The electrochemical investigations were evaluated to a glassy carbon electrode modified PEDOT: PSS in terms of the parameter of analytical performances including linearity, precision, detection limit and quantitation limit. Based on the results, the oxidation peak of thiamine observed at potential of 250 mV vs Ag/AgCl with its current intensity measured 2.5 times higher than detected using unmodified glassy carbon electrode. In addition, the measurement of thiamine in the concentration range of 1 – 10 mM using a glassy carbon modified PEDOT:PSS displayed a good value for several parameters such as linearity (R2= 0.9913), precision (percentage of relative standard deviation as 3.9%), and the detection and quantitation limit as 2.5×10-5 M and 7×10-5 M, respectively. As a comparison in real analysis, this developed method was then used to measure thiamine in the sample of commercial vitamin and showed the accuracy value as 95.86%. This value was then compared with the real value and showed a non-significant different when analysed with t-student test at the confidence interval of 95%.